Some factors involved in mechanical instrumentation in the root canal of a permanent tooth - Chapman, Cecil Edgar (The University of Edinburgh, 1969)
Endodontics can best be defined in the words of the preface of the Bulletin on Endodontics prepared by the University of Toronto Dental School, This states that "endodontics is the union of two Greek words 'endo' within and 'odontos' a tooth. The English equivalent of these two Greek words encompasses the practice of all therapeutic and surgioal procedures relating to the protection of the vital pulp, bioaechanical and biochemical treatment of the pathologically involved pulp and the material obliteration of the apace formerly containing that pulp". This investigation is, how¬ ever, only involved with one of these factors, namely, bioaechanical instrumentation.

As a result of the present investigation, it is possible to make definite conclusions regarding the manner in which the stages of mechanioal preparation and filling the root canal of a human per¬ manent tooth should be performed.

In Chapter 2 it was demonstrated that a oertain degree of dis¬ crepancy ocourred between the measured diameter of the various root canal instruments and the diameter stated by the manufacturer. It was also shown that the most important region of the root canal was the apical third region, corresponding to the terminal 6 rams of the instrument. In this region it was shown that the root canal reamer was slightly more accurate than the Hedstrom file and would therefore appear, from the manufacturing point of view, to be the instrument of choice for the mechanioal preparation of the canal. It was again demonstrated from the results obtained in Chapter 3 that the root canal reamer is the instrument of choice for preparing the canal. This was demonstrated by reason of the fact that the root canal reamer tended to prepare a circular root canal, whereas the Hedstrom file always tended to prepare the root oanal oval in shape whether the canal was circular or ovoid in circumference before mechanical pre¬ paration commenced. A circular root canal, especially in the apical third, is essential if a hermetic seal is to be obtained in this region. Hermetic seeling will not necessarily be assured in an ovoicL oanal if reliance has to be placed on the sealing properties of the oementing medium used to cement the root canal point into the canal because of the possibility of introducing air bubbles into the cement, either during the mixing process or during introduction of the cement into the canal. That this is a real hazard was shown -168- by the number of X-rays that revealed evidence of air bubbles in the oanal after the final point had been inserted (Page 150 of Chapter 6).

Therefore, on the count of accuracy of preparation of the canal and on the count of sealing properties of the root filling point, the root oanal reamer is a moire successful instrument than the Hedstrom file. It is suggested that use of the Hedstrom file should be limited to smoothing irregularities in the canal wall in the coronal third of the tooth - irregularities oaused during the oourse of the initial opening for access to the root canal.

Final sealing of a canal prepared by means of root canal reamers will be adequately obtained using matched gutta percha points, that is, matched to instrument size. It was shown in Chapter 5 that in almost all cases the diameter of the matched point was greater than the diameter of the equivalent instrument. It was also pointed out that this fact alone was desirable whenever using gutta percha as the obturating medium since this material has a certain amount of flexi¬ bility and compressibility and can be placed in position under some pressure, thus ensuring that the point adequately seals the prepared root canal. It was demonstrated that the difference in diameter between the prepared canal and the gutta percha point was small, enough, it is suggested, to allow compensation for aoourate fit by compression of the gutta peroha. Unfortunately in the oase of the vezy narrow canal gutta percha is too flexible to allow the point to be placed under force and so resort would have to be made to silver points.

In the instances where silver points can be used (narrow canals, poaterlor teeth) the difference in diameter tended to be smaller and more uniform over the long axis than the gutta pereha points and therefore, it is suggested, silver points would be more accurate in obturating properties. Unfortunately silver points cannot be used as the obliterating material in all oases of root canal therapy (for instance, where a post crown restoration is contemplated), nevertheless gutta percha points have been shown to provide adequate sealing properties when used as the obliterating agent in root canal therapy

In Chapter 4 it was pointed out that it was generally implied in the literature (Black (1917), Brady (1920), Curson (1966), Grayson (1909), Ingle (1965), Ktfrer (1966) and Sommer (1966)) that material from the oanal was expelled through the apioal foramen during the course of mechanical instrumentation within the root canal. It was also stated that this investigator could find no evidence that this statement had been demonstrated experimentally even though every endodontist has this aim constantly before him during the operation of preparation of the root canal. In the introduction to Chapter 4 two questions were posed: -

1, Did material from the root canal pass through the apical foramen during the act of preparation of the canal?

2, Was there a quantitative relationship between the amount of material expelled and the type of instrument used?

It has been demonstrated that the intuitive assumption that debris from the root canal was expelled through the apioal foramen during mechanical instrumentation was in fact true. It was -170- shown that in virtually all teeth investigated expulsion of material through the apex did occur whether* the root canal was prepared by means of the root canal reamer or the Hedstrom file. As far as the assumption that one instrument might be more traumatic than the other, it was demonstrated in this Chapter that this was not true, each instrument expelling as much material as the other. Therefore on this count alone the root canal reamer was not necessarily the instrument of ohoioe. However, on the other counts already discussed, it was shown to be the instrument of choice and therefore, in the final analysis, is to be desired instead of the Hedstrom file in the mechanical preparation of a root canal of a permanent tooth.

In Chapter 6, a study of radiographs of root fillings carried out by students of the Edinburgh Dental School showed that the results obtained for the assessment of true tooth length were not as good as was hoped and that the introduction of root canal sealer into the prepared root canal must be carried out more precisely to avoid the inclusion of air bubbles. It can be stated, that whenever root treatment is required on a permanent human tooth, mechanical preparation of the root canal should be carried out by means of root canal reamers and, whenever possible, the root canal should ideally be filled by means of silver points. Since this is not always clinically possible, gutta percha points do provide an adequate hermetic seal to the apical constriction of a permanent tooth in those cases where they must be used in place of silver points.